(untitled) (CIPEEX, 2022)
TO REPORT THE EXPERIENCE OF STUDENTS, FROM HEALTH AND EXACT SCIENCES, PARTICIPANTS OF THE SCIENTIFIC INITIATION PROGRAM (SI) AND THE IMPACT OF S IN THE CONSTRUCTION OF A SCIENTIFIC CURRICULUM AIMING AT ADMISSION TO GRADUATE STUDIES. AN EXPERIENCE REPORT, THROUGH DESCRIPTIVE AND OBSERVATIONAL METHODS BASED ON SCIENTIFIC PRODUCTIONS RECORDED IN THE LATTES CURRICULUM AS STRICTO SENSU GRADUATE STUDENTS ABOUT THEIR EXPERIENCES DURING THE GRADUATION PERIOD AS STUDENTS OF SCIENTIFIC INITIATION AT A PRIVATE HIGHER EDUCATION UNIVERSITY, LOCATED IN THE INTERIOR OF THE STATE OF GOIS. RESULT: IT IS KNOWN THAT THERE IS A GREATER PRACTICE OF STUDENTS IN THE HEALTH AREA ENTERING THE SI, HOWEVER, STUDENTS FROM BOTH AREAS, UPON COMPLETING THEIR GRADUATION, PRESENTED A CURRICULUM BASED ON THE TRIPOD OF EDUCATION: TEACHING, RESEARCH, AND EXTENSION WITH PUBLICATIONS OF ARTICLES, PARTICIPATION IN CONGRESSES, MONITORING AND MULTI AND INTERDISCIPLINARY EXPERIENCES. THE ACADEMICS PARTICIPATED IN THE SELECTION FOR THE PROMOTION OF SCHOLARSHIPS FOR THE STRICTO SENSU MASTER’S DEGREE POSTGRADUATE COURSE, WHERE THE PRODUCTIONS OF THE LAST 5 YEARS WERE EVALUATED, SUCH AS: CANDIDATE’S ACADEMIC PERFORMANCE DURING GRADUATION, PROVEN PREVIOUS INVOLVEMENT WITH RESEARCH ACTIVITIES (EXAMPLE, CONDUCTING SCIENTIFIC INITIATION INTERNSHIPS, OBTAINING RESEARCH GRANTS, PARTICIPATION IN SCIENTIFIC CONGRESSES AND MEETINGS, AWARDS AND INTERNSHIP ABROAD), QUALITY OF THE CANDIDATE’S SCIENTIFIC AND TECHNOLOGICAL PRODUCTION (EXAMPLE, SCIENTIFIC ARTICLES, ABSTRACTS IN CONGRESSES AND TECHNICAL TEXTS AND OF SCIENTIFIC DISSEMINATION), THE CANDIDATES WERE SUCCESSFUL. CONCLUSION: IT IS POSSIBLE TO SUGGEST THAT, REGARDLESS OF THE AREA OF €‹€‹ACTIVITY, IT IS POSSIBLE TO EXPAND NEW HORIZONS FROM THE DEVELOPMENT OF THE SI, WHERE THERE IS AN INCENTIVE FOR INTEGRAL CURRICULAR TRAINING, ENABLING THEM TO FOLLOW UP ON THE RESEARCH DEVELOPED, ON FUTURE STUDIES, AND ON THEIR INSERTION IN THE LABOR MARKET AIMING AT TEACHING AND CONSOLIDATING A CAREER AS A BRAZILIAN RESEARCHER.